Best practice in the diagnosis and management of urogenital tuberculosis - Ekaterina Kulchavenya (Therapeutic Advances in Urology, 2013)
Tuberculosis (TB) is a current public health problem, remaining the most common worldwide cause of mortality from infectious diseases. Urogenital tuberculosis (UGTB) is the second most common form of extrapulmonary TB in countries with severe epidemic situations and the third most common form in regions with a low incidence of TB. In this article we present the terminology, epidemiology and classification of UGTB, as well as describing the laboratory findings and clinical features and approaches to chemotherapy as well as surgery.